Do smoking, nutrition, alcohol use, and physical activity vary between regions in Germany? - results of a cross-sectional study - Josefine Atzendorf; Christian Apfelbacher; Elena Gomes de Matos; Kirsten Lochbühler; Daniela Piontek; Nicki-Nils Seitz; Ludwig Kraus (BMC, 2020)
Abstract Background Previous studies on lifestyle risk factors mainly focused on age- or gender-specific differences. However, lifestyle risk factors also vary across regions. Aim of the present study was to examine the extent to which prevalence rates of SNAP (smoking, nutrition, alcohol consumption, physical activity) vary between East and West Germany or North and South Germany. Methods Data came from the population-representative 2015 Epidemiological Survey of Substance Abuse (ESA) comprising 9204 subjects aged 18 to 64 years. To assess an east-west or south-north gradient, two binary logistic regression models were carried out for each SNAP factor. Results The logistic regression models revealed statistically significant differences with higher rates of at-risk alcohol consumption and lower rates of unhealthy nutrition in East Germany compared to West Germany. Significant differences between North and South Germany were found for at-risk alcohol consumption with higher rates of at-risk alcohol consumption in South Germany. Daily smoking and low physical activity were equally distributed across regions. Conclusions The implementation of measures reducing at-risk alcohol consumption in Germany should take the identified east-west and south-north gradient into account. Since the prevalence of unhealthy nutrition was generally high, prevention and intervention measures should focus on Germany as a whole instead of specific regions.